LEAF EPIDERMIS ANATOMY OF RICE PLANTIS (Oriza sativa L.) WITH DIFFERENT SALINITY TOLERANCE DEGREES - Sam, Ofelia D.; Falcon, Viviana; Rosa, Maria Cristina de la (REVISTA DE AGRICULTURA, 2015)
LEAF EPIDERMIS ANATOMY OF RICE PLANTIS (Oriza sativa L.) WITH DIFFERENT SALINITY TOLERANCE DEGREES